2001
DOI: 10.1111/1467-8462.00186
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Australia's Ethical Funds

Abstract: Australia's three major public ethical investment funds achieved mixed financial success in the seven years to 30 June 1998, though on average the funds underperformed relative to the market. For the four-year and five-year holding periods to 30 June 1995 and 1996 respectively, the average holding-period returns for the three funds were less than the risk-free rate. This is strong evidence of investors incurring a financial discount for investing ethically and, with respect to the ethical investor's utility fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 6 publications
5
58
0
1
Order By: Relevance
“…With this simple strategy, they earn an abnormally high return of 8.5 % per year. These findings correspond well with the explanation by Tippet (2001) that excluding firms where management behavior is considered unethical should lead to significant outperformance, because firms with unnecessary costs are avoided. Shank et al (2005) compare 11 firms that are well known for their SR behavior with selected SRI mutual funds and a conventional benchmark.…”
Section: Sr [ Conventional Portfolio Returnssupporting
confidence: 88%
See 3 more Smart Citations
“…With this simple strategy, they earn an abnormally high return of 8.5 % per year. These findings correspond well with the explanation by Tippet (2001) that excluding firms where management behavior is considered unethical should lead to significant outperformance, because firms with unnecessary costs are avoided. Shank et al (2005) compare 11 firms that are well known for their SR behavior with selected SRI mutual funds and a conventional benchmark.…”
Section: Sr [ Conventional Portfolio Returnssupporting
confidence: 88%
“…Kahn et al (1997) compare the performance of a tobacco-free S&P 500 portfolio with the complete S&P 500 portfolio and find underperformance for the tobaccofree portfolio between 1986 and 1996. In his study, Tippet (2001) shows significant underperformance of the three major Australian ethical mutual funds between 1991 and 1998 compared to their benchmarks. He holds higher transaction costs and management fees responsible for this underperformance.…”
Section: Sr \ Conventional Portfolio Returnsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the Australian context, there are relatively few studies such as those of (Bauer et al, 2006;Tippet, 2001;Cummings, 2000) which show that the performance of SRI is not significantly different with conventional investments while other studies (Jones et al, 2008) found SRI to be underperforming in the Australian context. None of these studies, however, have focused on the linkages or spill-over between SRI markets.…”
Section: Brief Review Of the Literaturementioning
confidence: 98%